2022
DOI: 10.3390/su15010015
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Thermal Treatment of the Black Mass from Spent Lithium-Ion Batteries

Abstract: Recycling lithium-ion batteries is crucial for the environment and the sustainability of primary resources. In this paper, we report on the characterization of two grades of black mass from spent lithium-ion batteries (with typical lithium–nickel–manganese–cobalt oxide cathode compositions) and their behavior during heating trials. This study paves the way for optimizing lithium-ion battery recycling processes by fully characterizing black mass samples before and after heating. A gas release under pyrolytic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…In an inert atmosphere, a mass loss detected by TGA will thus be associated with the release of CO and CO 2 that is correlated to the graphite content. This idea is in direct contrast to previously published studies using TGA under flowing air, 34 , 35 , 36 where uncontrolled combustion reactions take place, making it difficult to correlate mass changes with the BM composition. To develop the novel approach hereby proposed, TGA-EGA results were performed on artificial mixtures of graphite and cathode materials, i.e., Li(Ni 0.33 Mn 0.33 Co 0.33 )O 2 (NMC) or LiCoO 2 (LCO) at known compositions to produce standardized correlation functions.…”
Section: Introductionmentioning
confidence: 82%
“…In an inert atmosphere, a mass loss detected by TGA will thus be associated with the release of CO and CO 2 that is correlated to the graphite content. This idea is in direct contrast to previously published studies using TGA under flowing air, 34 , 35 , 36 where uncontrolled combustion reactions take place, making it difficult to correlate mass changes with the BM composition. To develop the novel approach hereby proposed, TGA-EGA results were performed on artificial mixtures of graphite and cathode materials, i.e., Li(Ni 0.33 Mn 0.33 Co 0.33 )O 2 (NMC) or LiCoO 2 (LCO) at known compositions to produce standardized correlation functions.…”
Section: Introductionmentioning
confidence: 82%
“…Emissions from technical processes can occur in two ways when recycling LIBs: reaction emissions and material losses. Reaction emissions are generated from chemical reactions during the process, such as thermochemical reactions [125]. Material losses, on the other hand, result from the release of components of the batteries during the recycling process.…”
Section: Environmental Aspectsmentioning
confidence: 99%
“…Moreover, two common thermal processes are used to degrade the binder, calcination and pyrolysis, and an overview of industrial recycling routes can be found in [14]. Pyrolysis is more effective than calcination in preventing undesired graphite decomposition due to the absence of oxygen in the atmosphere [6,[15][16][17][18], which is one particular reason for our focus on pyrolysis conditions in this work. In order to tailor the binder degradation during the thermal treatment of black mass, efficient computational methods are necessary to optimize future thermal treatment processes and adapt flexibly to changing feeds in the recycling route.…”
Section: Introductionmentioning
confidence: 99%